Cooperative Transmission Scheme Using the Single Antenna in the Broadcasting and Cellular System - Yang, Hyun-Jee; Kwon, Bit-Na; Baik, Jung-In; Song, Hyoung-Kyu (Wireless personal communications, 2017)
In this paper, the cellular system and broadcasting system use a cooperative transmission scheme. The conventional scheme is not consider the condition of a channel between a cellular base station (CBS) and a destination user. In this conventional scheme, two CBSs communicate with the user by the cooperative transmission scheme when the user is located in the cell edge. If CBS is distant from a user and the channel condition is poor, the performance of communication is degraded. The proposed scheme using the relay between CBS and the user located in the edge of CBSs improves the performance of the communication when the channel state between CBS and the user is bad. Also, space time block code and cyclic delay diversity scheme are used for the reliable transmission in the proposed scheme. The proposed scheme using the relay achieves good BER and throughput performance. Through the simulation, it is confirmed that the proposed scheme is better than the conventional scheme.